Antegrade approach for TAVR with total occlusion of the descending aorta. Issue 5 (13th November 2013) - Levisay, Justin P.; Salinger, Michael H.; Feldman, Ted
<x xml:space="preserve">Abstract</x> The antegrade approach for aortic valve interventions is well known but has not been widely used for transcatheter aortic valve replacement (TAVR) procedures. We encountered a patient with no possibility of retrograde access due to a totally occluded abdominal aorta who had a failed attempt at apical TAVR. We describe antegrade TAVR despite occlusion of the abdominal aorta, with the arterial limb of the requisite veno‐arterial loop created using bilateral arm access, a novel version of the previously described antegrade approach. © 2013 Wiley Periodicals, Inc.